2022
DOI: 10.1002/jmv.28059
|View full text |Cite
|
Sign up to set email alerts
|

Associated microbiota and treatment of severe fever with thrombocytopenia syndrome complicated with infections

Abstract: The purpose of this study is to assess the incidence and management of coinfections in hospitalized severe fever with thrombocytopenia syndrome bunyavirus (SFTSV) patients. We retrospectively evaluated the microbiological database records of the SFTS patients in the first affiliated hospital of Anhui Medical University from January 1, 2018, to December 1, 2021. According to the obtained results, coinfections including pulmonary infection, bloodstream infection, biliary tract infection, urinary tract infection,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 17 publications
1
13
2
Order By: Relevance
“…Recent studies have reported the significantly high incidence of co‐infections in SFTS, and these studies suggested consistently that respiratory infections were predominant and should be of sufficient concern 6,7 . SFTSV can cause cytokine storm and immunosuppression in severe cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported the significantly high incidence of co‐infections in SFTS, and these studies suggested consistently that respiratory infections were predominant and should be of sufficient concern 6,7 . SFTSV can cause cytokine storm and immunosuppression in severe cases.…”
Section: Introductionmentioning
confidence: 99%
“…5 Recent studies have reported the significantly high incidence of co-infections in SFTS, and these studies suggested consistently that respiratory infections were predominant and should be of sufficient concern. 6,7 SFTSV can cause cytokine storm and immunosuppression in severe cases. It has been demonstrated that fatal patients were more biased towards negative immune modulation, including significantly increased Th17 and decreased CD4 + T lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, our sample size is the largest among previously published reports. A study on SFTS from the First Affiliated Hospital of Anhui Medical University included 160 patients with SFTS 28 . Another multicenter cohort study from 13 university hospitals in Korea included 142 patients with SFTS 27 .…”
Section: Discussionmentioning
confidence: 99%
“…A study on SFTS from the First Affiliated Hospital of Anhui Medical University included 160 patients with SFTS. 28 Another multicenter cohort study from 13 university hospitals in Korea included 142 patients with SFTS. 27 In addition, a study on SFTS conducted in Nanjing included 256 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive pulmonary aspergillosis (IPA), which is thought to be one of the most frequent infections in SFTS patients, widely develops in immuno-compromised people and has been found to increase the mortality of SFTS according to several studies (Sakaguchi et al, 2019;Iwao et al, 2021;Ge et al, 2022). The incidence of IPA in SFTS is ∼20%, while the mortality of these cases is between 20 and over 50% (Bae et al, 2020;Hu et al, 2021;Xu et al, 2021;Zhang et al, 2022). A study from China reported that patients who received early antifungal treatment tended to have improved survival rates, which indicated the necessity of early diagnosis and timely treatment (Hu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%